A new species of fig-feeding Lonchaeidae (Diptera: Schizophora) from India and a checklist for the family in the Indian sub-continent - Macgowan, Iain; Razak, Nakeer; Rotheray, Graham E.; Ahmad, Irfan (Zootaxa, 2012)
A new species of Lonchaeidae, Silba lashker sp. nov. is described from specimens reared from figs in Jammu and Kash-mir, India. The adult and larvae are described and comparisons are made with other species in the genus. A checklist forthe Indian sub-continent is provided which lists twenty four species in four genera including one new species and a furtherfour species recorded from the sub-continent for the first time. The family Lonchaeidae is reported for the first time from the biodiversity hotspot region of the Kashmir valley.